Writing for equality: a comparative study of the writings of Wollstonecraft, Schreiner and Woolf on the status of women - Morgan, Yvette Margaret (University of the Free State, 2007)
Patriarchy has tainted the mind of society, thereby creating gender discrimination and inequality. Until recently, this bias against women filtered down to women writers too. This MA dissertation is a comparative study of the works of Mary Wollstonecraft, Olive Schreiner and Virginia Woolf in their socio-historical context. While Wollstonecraft and Woo If lived in Britain, Schreiner spent most of her life in South Africa. It is interesting to observe that these three writers, working in two different countries, Britain and South Africa, shared strong ideas on women and education, double standards in society, professions for women and the roles of women in society. While sharing ideas, each writer lived in her own unique milieu and thus held certain beliefs more strongly than others. By evaluating women's literature dating from the late 18th century, this dissertation examines the evolution of women's situation in society and obtains, for the reader, a sense of what social issues were relevant at the time and how these issues have changed and/or stayed the same. The three authors chosen were also influenced by their predecessors' thoughts, which is clear in their literature. By looking at their work in the context of society and the influence of previous feminist literature, the reader can see the power that their thoughts and words hold. Though some of the problems about which these authors wrote so tellingly (for example, inequality under the law) have become redundant in Western society, many of the issues addressed in their writing have formed the baseline of feminist beliefs and are still very relevant today.
Dissertation (M.A. (English and Classical Languages))--University of the Free State, 2007
Keywords: Olive Schreiner; Mary Wollstonecraft; Virginia WooIf; Women's Rights; Sexual Double Standards; Women and Education; Women and the Professions; Women in the 1700s; Women in the 1800s; Women in the 1900s; Woolf, Virginia,1882-1941 -- Criticism and interpretation; Wollstonecraft, Mary,1759-1797 -- Criticism and interpretation; English literature -- Women authors -- History and criticism; Women and literature -- Great Britain